(3eHGOF GdNWQ hGdJGejfs - (3eNJGQ eMehO(B, (3GdgGTejs; (3MehOI GHQGgje YHO GdfHj (B, s ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI dWHY h GdfTQhGdJhRjY(B,s, 2001)
(3GdNWQ hGdJGejfGJ GdGLJeGYjI (B2- (3GdJGejf Ydi GdMjGI a(B1 (3aj LhGfH JJYdb HGdNWQ aj bjGS GdNWQ hGOGQJg aj GdGWGQ GdYGe ddJGejf (B2- (3aj GdGWGQ GdYGe ddJGejf GdGLJeGYj (B3- (3aj GdbGfhf GdLOjO ddJGejfGJ GdGLJeGYjI (B4- (3aj fXGe GdecGaGI GdLOjO WHbG ddbGfhf Qbe (B47 (3dSfI (B1984 (3LOGhd hGMJeGdGJ GdMjGI GdaUd GdKGfj ebOeI aj JCejfGJ GdMjGI GdaUd GdKGdK (B: (3MSGH GdGbSGW dHQHMjI GdUGajI (B.s
Keywords: (3eHGOF GdNWQ (B- (3eHGOF GdJGejfs